Factors Affecting Age of Menarche: A Cross-Sectional - Aisy, Jihan Rohadatul; Pamungkasari, Eti Poncorini; Murti, Bhisma (Journal of Maternal and Child Health, 2024)
Background: Early menarche or first menstruation has been associated with increased risk of breast cancer and cardiovascular disease. Understanding the factors that influence the age of menarche is very important to provide promotive and preventive actions that can be carried out by schools and families. This study aims to analyze the factors that influence the age of menarche. Subjects and Method: This study used an observational analytical study with a cross-sectional design. The subjects in this study were 125 female students at 5 public elementary schools in Malang City, East Java, Indonesia. The dependent variable was the age of menarche. The independent variables were nutritional status (BMI), stress, parenting patterns, and parenting pattern dominance. Data analysis used univariate, bivariate, and multivariate models with multiple linear regression methods. Results: Age of menarche decreased with stress (b = -0.50; 95% CI = -0.70 to -0.29; p <0.001), BMI ≥25 (b= -9.00; 95% CI = -16.75 to -1.25; p = 0.023), authoritarian parenting style (b = -1.05; 95% CI = -1.53 to -0.58; p<0.001), and the dominance of parenting patterns by single parents or guardians (b= -4.92; 95% CI = -9.42 to -0.42; p = 0.032). The age of menarche was higher in adolescents with a lower BMI than a normal BMI (b = 4.78; 95% CI = 1.20 to 8.36; p = 0.009). This multiple linear regression analysis model showed moderate model suitability with an Adj R-Squared value of 46.81%. Conclusion: Multiple linear regression analysis showed a relationship between stress factors, authoritarian parenting patterns, dominant parenting patterns, and BMI with a decrease in the age of menarche which was statistically significant.